2004
DOI: 10.1016/j.mod.2004.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of the genes involved in fin regeneration and blastema formation in the medaka, Oryzias latipes

Abstract: Medaka is an attractive model to study epimorphic regeneration. The fins have remarkable regenerative capacity and are replaced about 14 days after amputation. The formation of blastema, a mass of undifferentiated cells, is essential for regeneration; however, the molecular mechanisms are incompletely defined. To identify the genes required for fin regeneration, especially for blastema formation, we constructed cDNA libraries from fin regenerates at 3 days postamputation and 10 days postamputation. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 36 publications
1
68
0
Order By: Relevance
“…Consistent with Katogi et al (2004) who found SOCS3 (identified as olrf30i08) expressed at higher levels at day 3 postamputation vs. day 10 postamputation in regenerating Medaka fins, we find that the induced expression of SOCS3 declines 14-fold from 1dPA to 5dPA at the regeneration-complete stage. However, at the regeneration-incomplete stage, the decline in expression is only 1.3-fold (Katogi et al, 2004).…”
Section: Activity Of Immune Response/inflammationrelated Genes Duringsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with Katogi et al (2004) who found SOCS3 (identified as olrf30i08) expressed at higher levels at day 3 postamputation vs. day 10 postamputation in regenerating Medaka fins, we find that the induced expression of SOCS3 declines 14-fold from 1dPA to 5dPA at the regeneration-complete stage. However, at the regeneration-incomplete stage, the decline in expression is only 1.3-fold (Katogi et al, 2004).…”
Section: Activity Of Immune Response/inflammationrelated Genes Duringsupporting
confidence: 91%
“…The results of eight previously published regeneration-related genomic analyses were selected for comparison to the microarray results (Ishino et al, 2003;King et al, 2003;Summan et al, 2003;Katogi et al, 2004;Swamy et al, 2004;Wolfe et al, 2004;Reddien et al, 2005;Schnapp et al, 2005;Tazaki et al, 2005). Due to the variety of organisms studied in these articles and the information provided, different approaches were taken to compare them to the Xenopus data.…”
Section: Comparisons To Previously Published Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the efficiency of knock-down varies greatly between morpholinos, it would be difficult to argue for using this technique to compare which of two genes has a greater effect on fin outgrowth. However, as the expression of new molecules during regeneration are being identified in microarray or differential display screens, this technique does permit placing these molecules into known regeneration pathways and revealing the functional relevance of these genes for regeneration (Katogi et al, 2004;Padhi et al, 2004). For example, knock-down of Msxb did not effect msxc expression at 3 days post-amputation, but both msxb and msxc expression were greatly reduced or absent when Fgfr1 levels were knocked-down (Poss et al, 2000; Fig.…”
Section: Discussionmentioning
confidence: 99%